ALK fusion variant 3a/b, concomitant mutations, and high PD-L1 expression were associated with unfavorable clinical response to second-generation ALK TKIs in patients with advanced ALK-rearranged non-small cell lung cancer (GASTO 1061). (March 2022) - Li, Meichen; Hou, Xue; Chen, Jing; Zhang, Baishen; Wang, Na; Han, Hongyu; Chen, Likun
Highlights: Second-generation ALK TKIs have been the standard treatment in advanced ALK -rearranged NSCLC, but clinical responses vary widely. High PD-L1 expression was associated with ALK fusion variant 3a/b and concomitant mutations in ALK -rearranged NSCLC. ALK fusion variant 3a/b, concomitant mutations, and high PD-L1 expression were associated with unfavorable clinical response to second-generation ALK TKIs in ALK -rearranged NSCLC. Abstract: Objectives: Second-generation anaplastic lymphoma kinase (ALK) tyrosine kinase inhibitors (TKIs) have significantly improved clinical outcomes in patients with advanced ALK -positive non-small cell lung cancer (NSCLC), but clinical responses vary widely. In this study, the impacts of ALK fusion variants, concomitant mutations, and PD-L1 expression on the clinical response were evaluated in patients receiving second-generation ALK TKIs. Materials and methods: We retrospectively enrolled 193 patients with ALK -rearranged advanced NSCLC who received second-generation ALK TKIs at Sun-yat Sen University Cancer Center from January 2015 to December 2020. The ALK fusion variants and concomitant mutations were identified with next-generation sequencing, while PD-L1 expression was assessed by immunohistochemistry. Results: The median progression-free survival (PFS) was significantly shorter for variant 3a/b than for other variants (9.93 months vs 16.97 months, HR 1.941, P = 0.0014). Baseline concomitant mutations were significantly associated with shorter PFS while on ALK TKIs (median PFS, 10.87 months vs 22.47 months, HR 1.984, P = 0.002). A subset of 68 patients was analyzed for PD-L1 expression: TPS 0% in 32.4% (22/68) of the patients, 1–49% in 30.9% (21/68) of the patients, and ≥ 50% in 36.7% (25/68) of the patients. Expression of PD-L1 was significantly associated with variant 3a/b and concomitant mutations. Median PFS was shorter in patients with high PD-L1 expression (median PFS in patients with PD-L1 TPS of 0% vs 1–49% vs ≥ 50% were 27.43 months vs 30.63 months vs 9.50 months, respectively, P = 0.001). In multivariate analysis, PD-L1 expression (TPS ≥ 50%), concomitant mutations, and variant 3a/b remained negative prognostic factors for the clinical efficacy of second-generation ALK TKIs in ALK-rearranged non-small cell lung cancer. Conclusion: ALK fusion variant 3a/b, concomitant mutations, and high PD-L1 expression were associated with unfavorable clinical response to second-generation TKIs in ALK -rearranged NSCLC.